Uniformly aligned liquid crystal molecules on reformed poly(ethylene-co-vinyl acetate) layers driven by ion beam exposure. Issue 2 (26th January 2022) - Lee, Dong Wook; Kim, Eun Mi; Heo, Gi Seok; Lee, Ju Hwan; Kim, Dong Hyun; Oh, Jin Young; Jang, Jong In; Eom, Sung Jin; Jeong, Hae-Chang; Seo, Dae-Shik
ABSTRACT: The characteristics of a poly(ethylene-co-vinyl acetate) (PEVA) film formed by spin coating process and ion beam (IB) irradiation was investigated with irradiation times. A physicochemical analysis was used to analyse the suitability of the PEVA film as a uniform liquid crystal (LC) alignment layer. Atomic force microscopy (AFM) revealed an increased surface roughness after IB irradiation. X-ray photoelectron spectroscopy (XPS) analysis showed IB irradiation broke the polymer branches and increased the oxygen concentration and bonding on the surface. These derived the strong Van der Waals forces and dipole-dipole interactions between the PEVA surface and LCs. The IB irradiation generated surface anisotropy on the PEVA film and unidirectional LC alignment was achieved. Polarised optical microscopy (POM) and pre-tilt angle measurements were carried out to show the uniform LC alignment. The transmittance curve exhibited a high optical performance. These results show the promising capabilities of IB irradiated PEVA film as an alignment layer in LC displays. Graphical asbtract: uf0001